Nilai dan Makna Budaya A’coto pada Pernikahan Masyarakat Desa Julu Bori Kabupaten Gowa - Mrs. Nurhikmah; Mubarak Dahlan (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to find out: (1) How are the efforts made by the people of Julubori Village, Pallangga District, Gowa Regency in maintaining a'coto culture. (2) The value and meaning of a'coto culture in the people of Julubori Village, Pallangga District, Gowa Regency. To achieve this goal, the researchers used data collection techniques through observation, interviews and documentation. The data obtained from the research results were processed using qualitative analysis with a descriptive-analytic approach to the implementation of a'coto culture in the people of Julubori Village, Pallangga District, Gowa Regency. Based on the results of this study indicate that, (1) The efforts made by the people of Julubori Village in maintaining a'coto culture are by continuing to practice it and teaching their children as the next generation about the traditions or habits passed down from their ancestors. (2) The values ​​and meanings of the a'coto culture in the people of Julubori Village, namely the kinship values, mutual cooperation values ​​and economic values. The meaning contained in the implementation of a'coto culture is a form of gratitude to God Almighty because he is still given fortune and trust in its implementation.